TEACHING MIS-DERIVED WORDS IN TURKISH - Demir, Erkan (International Online Journal of Education and Teaching, 2024)
In this study, within the scope of teaching mis-derived words in Turkish, the mis-derived words are analyzed to understand which suffixes the Turkish words are derived and to use the language consciously. In education, many mis-derived words in Turkish originating from various forms and needs over time are encountered. It is of great importance to understand the Turkish language well and to teach the structure of the language, its suffixes and roots, and how words are derived. In the second quarter of the 20th century, hundreds of new words derived in place of old Arabic and Persian origin words began to be widely used, especially with the simplification and Turkization flow in the language. In addition, many new words have been derived from Turkish roots with suffixes for new objects and concepts that have entered human life with the developing technology instead of directly taking the words of Western origin. Although deriving new words for new objects and ideas has responded to a need, it is not possible to say that all of these newly derived words are generally accepted and used, unlike the words that arise naturally in the natural flow of life; however, many of them have become widespread and have taken their place in the language system. However, what is more remarkable than that is that some of these newly derived words are derived with suffixes (-ay+ / -ey+, -ceme+, +de+, +dem+, +em+, +et+, -et+, -ev+, +ge+, -ge-, +gen+, +gü+, +gün+ / +kin+, +m+, + (ı)ntı+, -sa-, +tay+, -v+, -y+, +y+) are not current in Turkish. In this study, what is meant by the wrongly derived word is the words derived with these suffixes that are not current in Turkish. The reasons for these wrong derivations have not been examined in detail here since they will be the subject of a separate study; only it is said that they arise with a wrong derivation with suffixes that are not found in Turkish or why some words that are allegedly derived incorrectly cannot be considered incorrect.